PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA SDM DAN KUALITAS LULUSAN MAHASISWA DI POLITEKNIK ABCD JAKARTA - Darmawan; Jaenudin Akhmad; Endah Heryanti; Subagiyo; Rini Mardikawanty (POLITEKNIK LP3I JAKARTA, 2025)
This study discusses the influence of leadership style on human resource (HR) performance and the quality of student graduates at ABCD Jakarta Polytechnic. This study aims to analyze the impact of leadership style applied by institutional leaders on HR performance and the quality of student graduates. The research method used is a qualitative method with a descriptive approach. Data were collected through questionnaires distributed to lecturers, administrative staff, and students, as well as in-depth interviews to gain further perspectives. The results of the study indicate that the dominant authoritarian leadership style in this institution contributes to employee performance which is only at a moderate level and the quality of graduates that is not optimal. In contrast, transformational and participatory leadership styles have been shown to have a significant positive influence in increasing motivation, HR performance, and graduate quality. The main recommendation of this study is the need for a shift in leadership style from authoritarian to a more inclusive and supportive style to improve overall institutional performance.